Creation as Episteme of Transdiscipline Acmeology - Palamarchuk, Yevhen; Mudrakov, Vitaliy (Pedagogical Discourse, 2012)
The article deals with the characteristics and phenomenon of art’s peculiarity. It determinates it’s place and role as episteme of transdiscipline acmeology.